Single best answer MCQs in anaesthesia - Mendonca, Cyprian; Chaudhari, Mahesh; James, Josephine (Tfm Pub., 2010)
Suitable for assessing a trainee's clinical skills and problem-solving abilities, this title allows the trainee to demonstrate application of their knowledge to clinical practice. It comprises six sets of practice papers. Each set contains 30 single best answer questions which cover topics including clinical anaesthesia, pain and intensive care.